A critical review on enhancement and sustainability of energy systems: perspectives on thermo-economic and thermo-environmental analysis - Oyedepo, Sunday O.; Waheed, Mufutau A.; Abam, Fidelis I.; Dirisu, Joseph O.; Samuel, Olusegun D.; Ajayi, Oluseyi O.; Somorin, Tosin; Popoola, Abimbola P. I.; Kilanko, Oluwaseun; Babalola, Philip O. (Frontiers in Energy Research, 2025)
Given the increased natural resource consumption of contemporary energy conversion systems, as well as the emissions, waste disposal, and climate changes that accompany them, a critical review of new techniques -known as thermo-economic and thermo-environmental analyseshas been carried out for the evaluation and optimization of energy conversion processes, from the perspectives of thermodynamics, economics, and the environment. Such a review study is essential because of the energy system's impacts on sustainability and performance management requirements, and more importantly, it is crucial to understand the whole picture of performance evaluation of energy systems from the sustainability perspective. The study evaluated the performance and optimization of energy systems and examined the different approaches that integrate the economic, environmental, and second law of thermodynamics for sustainable development. Moreover, to assess the technical, economic, and environmental worth of energy systems and guarantee that the chosen designs are well-suited to a sustainable development framework, a mix of thermodynamic, economic, and environmental indicators is taken into consideration. In this regard, thirteen sustainability indicators for the design, analysis, and performance improvement of energy systems from the viewpoints of thermodynamics, economics, and the environment are presented and discussed. The outcome of this study shows that (i) the sustainability of energy conversion systems can be enhanced with the use of exergy techniques assessment; (ii) by reducing energy losses, exergy efficiency initiatives can lessen their adverse effects on the environment; (iii) the best methods for efficient use of energy resources, low energy production costs, and less environmental impact can be provided by hybrid energy systems; and (iv) use of a single performance metric to optimize the energy process results in improbable outcomes. Hence, multi-criteria techniques should be utilized, allowing for a more comprehensive optimization and planning of sustainable energy systems. Researchers and field engineers working on energy systems' design, modeling, assessment, and performance optimization would find great value in this comprehensive review study.